Analisis Hubungan Antara Kecerdasan dan Kesiapan Sekolah Pada Siswa Preschool di Sekolah X - Sri Ratnawati; Ika Apriati Widya Puteri; Ratnasartika Aprilyani; Anna Mariani Kartasasmita (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to analyze the relationship between intelligence level and school readiness in children aged 5–7 years who are about to enter elementary school. A total of 139 students participated, completing an intelligence test using the Coloured Progressive Matrices (CPM) and a school readiness test using the Nijmeegse Schoolbekwaamheids Test (NST). Results showed that most students had intelligence levels in the Grade I/Superior category (72%), Above Average (13%), Average (10%), Below Average (1%), and Mentally Deficient (4%). NST results indicated that 81% of students were classified as ready, 6% as undecided, and 14% as not ready. Less optimal readiness aspects included understanding numbers and comparisons, concentration, body awareness, fine motor skills, shape recognition, and story comprehension. Statistical analysis showed a Sig. value of 0.293 > 0.05, indicating no significant relationship between CPM and NST scores. These findings suggest that intelligence alone does not directly determine school readiness; other factors such as parenting style, developmental stimulation, physical health, motivation, and learning experiences also play a significant role. The study recommends holistic interventions that address both cognitive and non-cognitive skills to better prepare children for primary education.